Pengembangan Media Video Pembelajaran Mata Pelajaran Pendidikan Jasmani, Olahraga dan Kesehatan Kelas X SMA - Azmi, Rahmatul; Syafril, Syafril; Rayendra, Rayendra; Masnur, Al-Kadri (Indo-MathEdu Intellectuals Journal, 2024)
Analysis of the learning process shows several obstacles, including the use of suboptimal learning media, students' difficulties in mastering the material, and time limitations. Therefore, this study aims to develop video media as an effort to overcome these obstacles. This type of research is development research known as Research and Development (R&D) with a 4-D development model. This study uses quantitative data analysis techniques. The data used is the data from validation by one material expert and two media experts. The practicality test was carried out to 30 students of SMAN 1 Suliki District as many as 30 students in class X to test the practicality of the learning video products developed. The results of the material validation test showed an average of 4.86 categorized as "very valid", the results of the validation of two media experts in a row obtained an average score of 4.93 and 4.79 categorized as "Very Valid". Furthermore, the results of the product practicality test carried out are in the "practical" category for use with an average score of 4.36. Based on the results of the validity test and practicality test, it can be concluded that the learning video product developed is valid and practical and can be used in the learning process